Hydrosalpinx - Ayurveda Management - A Case Report - Dhiman, Kamini (International Research Journal of Ayurveda & Yoga, 2021)
A case is reported of a 30 years old female patient wants to conceive for 12 years. Patient specified the complaint as pain abdomen. Patient underwent examinations and diagnostic investigations to rule out the cause. She was found to have Hydrosalpinx in her Ultrasonography finding. The treatment was planned accordingly, and the regimen according to Ayurveda principle was planned, comprising correction of Kshetra DushtithroughMridu Shodhana And Shamana therapy. Ultrasonography was repeated after 12 weeks of the treatment wherein hydrosalpinx was found as resolved.